Small RNAs in the Antarctic bacterium Pseudomonas extremaustralis responsive to oxygen availability and oxidative stress - Solar Venero, Esmeralda Clara; Matera, Gianluca; Vogel, Jörg; López, Nancy Irene; Tribelli, Paula Maria (Environmental Microbiology Reports)
Bacterial small non-coding RNAs (sRNAs) play key roles as genetic regulators, mediating in the adaptability to changing environmental conditions and stress responses. In this work, we analysed putative sRNAs identified by RNA-seq experiments in different aeration conditions in the extremophile bacterium P. extremaustralis. These analyses allowed the identification of 177 putative sRNAs under aerobiosis (A), microaerobiosis (M) and microaerobiosis after H2O2 exposure (m-OS). The size and transcription profile of eight sRNAs with differential expression were verified by Northern blot. sRNA40, with unknown function but conserved in other Pseudomonas species, was selected to perform overexpression experiments followed by RNA-seq analysis. The overexpression of sRNA40 in P. extremaustralis resulted in significant expression changes of 19 genes with 14 differentially upregulated and five downregulated. Among the upregulated genes, eight transcripts corresponded to components of secretion systems, such as gspH, gspK, and gspM, belonging to the Type II secretion system, and rspO and rspP from Type III secretion system. Our results showed a novel sRNA which expression was triggered by low oxygen levels, and whose overexpression was associated with upregulation of selected components of protein secretion systems. Fil: Solar Venero, Esmeralda Clara. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales; Argentina Fil: Matera, Gianluca. Universität Würzburg; Alemania Fil: Vogel, Jörg. Universität Würzburg; Alemania Fil: López, Nancy Irene. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y ...